Prevalence of ten LRRK2 variants in Parkinson's disease: A comprehensive review. (May 2022) - Simpson, Christopher; Vinikoor-Imler, Lisa; Nassan, Feiby L.; Shirvan, Julia; Lally, Cathy; Dam, Tien; Maserejian, Nancy
Abstract: Introduction: Variants in the leucine-rich repeat kinase 2 gene ( LRRK2 ) are risk factors for Parkinson's disease (PD), but their prevalence varies geographically, reflecting the locations of founder events and dispersion of founders' descendants. Methods: A comprehensive literature review was conducted to identify studies providing prevalence estimates for any of ten variants in LRRK2 (G2019S, R1441C, R1441G, R1441H, I2020T, N1437H, Y1699C, S1761R, G2385R, R1628P) among individuals with PD globally. We calculated crude country-specific variant prevalence estimates and, when possible, adjusted estimates for ethno-racial composition. For clinic-based studies, probands were used over other familial cases, whereas for population-based studies, all PD cases were used. Results: The analysis included 161 articles from 52 countries yielding 581 prevalence estimates across the ten variants. G2019S was the most common variant, exceeding 1.0% in 26 of 51 countries with estimates. The other variants were far less common. G2385R and R1628P were observed almost exclusively in East Asian countries, where they were found in ∼5–10% of cases. All prevalence estimates adjusted for ethno-racial composition were lower than their unadjusted counterparts, although data permitting this adjustment was only available for six countries. Conclusions: Except for G2019S, the LRRK2 variants covered in this review were uncommon in most countries studied. However, there were countries with higher prevalence for some variants, reflecting the uneven geographic distribution of LRRK2 variants. The fact that ethno-racial group‒adjusted estimates were lower than crude estimates suggests that estimates derived largely from clinic-based studies may overstate the true prevalence of some LRRK2 variants in PD. Highlights: Variants in leucine-rich repeat kinase 2 (LRRK2) are linked to Parkinson's disease. Prevalence of Parkinson's disease mutations vary by geography and race/ethnicity. Adjustment for ethnoracial composition affects country-level prevalence estimates. G2019S was the most common LRRK2 variant across 51 countries.